Esophageal variceal bleeding in hospitalized patients with cirrhosis. Issue 7 (14th May 2015) - Pant, Chaitanya; Desai, Madhav; Deshpande, Abhishek; Taylor, Ryan; Olyaee, Mojtaba; Gilroy, Richard
<x xml:space="preserve">Abstract</x> Esophageal variceal bleeding (EVB) is a frequent complication in cirrhotic patients resulting in considerable mortality and morbidity. The aim of this study was to investigate the occurrence, impact, and trends of EVB in hospitalized cirrhotic patients on a nationwide level in the United States. We interrogated data from the Nationwide Inpatient Sample from 2002 to 2012. Utilizing International Classification of Diseases, Ninth Revision, Clinical Modification codes, we analyzed hospital discharges for cirrhosis and related EVB in adult patients. EVB in cirrhotic patients was independently associated with overall worse outcomes with respect to in‐hospital mortality (10% vs 5%; P < 0.01) and hospital charges (median $41, 000 vs $26, 000; P < 0.01). In the period from 2002 to 2012, the number of cirrhosis‐related hospitalizations increased from 337, 956 to 570, 220 (P < 0.01). Concurrently, the incidence of EVB in hospitalized cirrhotic patients declined from 8.60% to 5.78%, with an overall decreased trend (P < 0.01). The decline in the rate of EVB in hospitalized cirrhotic patients from 2002 to 2012 likely reflects the effectiveness of primary and secondary prophylaxis. Journal of Hospital Medicine 2015;10:453–456. © 2015 Society of Hospital Medicine